Divergent activity of the gonadotropin-releasing hormone receptor gene promoter among genetic lines of pigs is partially conferred by nuclear factor (NF)-B, specificity protein (SP)1-like and GATA-4 binding sites. Issue 1 (December 2016) - McDonald, Emily; Smith, Jacqueline; Cederberg, Rebecca; White, Brett
Abstract Background Binding of gonadotropin-releasing hormone (GnRH) to its receptor (GnRHR) on gonadotropes within the anterior pituitary gland is essential to reproduction. In pigs, the GnRHR gene is also located near a genetic marker for ovulation rate, a primary determinant of prolificacy. We hypothesized that pituitary expression of the GnRHR gene is alternatively regulated in genetic strains with elevated ovulation rates (Chinese Meishan and Nebraska Index) vs. standard white crossbred swine (Control). Methods Luciferase reporter vectors containing 5118 bp of GnRHR gene promoter from either the Control, Index or Meishan swine lines were generated. Transient transfection of line-specific, full length, deletion and mutation constructs into gonadotrope-derived αT3-1 cells were performed to compare promoter activity and identify regions necessary for divergent regulation of the porcine GnRHR gene. Additionally, transcription factors that bind the GnRHR promoter from each line were identified with electrophoretic mobility shift assays (EMSA). Results Dramatic differences in luciferase activity among Control, Index and Meishan promoters (19-, 27- and 49-fold over promoterless control, respectively;P  < 0.05) were established. A single bp substitution (−1690) within a previously identified upstream enhancer (−1779/−1667) bound GATA-4 in the Meishan promoter and the p52/p65 subunits of nuclear factor (NF)-κB in the homologous Control/Index promoters. Transient transfection of vectors containing block replacement mutations of either the GATA-4 or NF-κB binding sites within the context of their native promoters resulted in a 50 and 60 % reduction of luciferase activity, respectively (P  < 0.05). Furthermore, two single-bp substitutions in the Meishan compared to Control/Index promoters resulted in binding of the p52 and p65 subunits of NF-κB and a specificity protein 1 (SP1)-like factor (−1235) as well as GATA-4 (−845). Vectors containing the full-length Meishan promoter harboring individual mutations spanning these regions reduced luciferase activity by 25 and 20 %, respectively, compared to native sequence (P  < 0.05). Conclusions Elevated activity of the Meishan GnRHR gene promoter over Control/Index promoters in αT3-1 cells is partially due to three single nucleotide polymorphisms resulting in the unique binding of GATA-4 (−1690), the p52/p65 subunits of NF-kB in combination with a SP1-like factor (−1235), and GATA-4 (−845).